PENYULUHAN HUKUM TENTANG NARKOTIKA “SAY NO TO DRUGS : EDUKASI DALAM MEMBANGUN KESADARAN HUKUM DAN KARAKTER ANTI NARKOBA DI KALANGAN SISWA SMA NEGERI 1 PERHENTIAN RAJA” - Mhd. Kastulani; Febri Handayani; Lysa Angrayni; Muhammad Darwis; Martha Hasanah Rustam (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Illegal drug trafficking in Indonesia is growing rapidly, supported by the progress and development of information and technology. Drug abuse in Indonesia is increasingly worrying. This statement is reinforced by the results of a national survey on the prevalence of drug abuse in 2023 conducted by the National Research and Innovation Agency (BRIN) in collaboration with the National Narcotics Agency (BNN) which showed that the prevalence of drug abuse reached 1.73 percent or equivalent to 3.3 million people from the total population aged 15-64 years. This figure also shows an increase in drug abuse at the age of 15-24 years, which is the zillennial generation (Gen Z). Gen Z or teenagers are the main target of drug dealers because Gen Z is considered a very vulnerable and impressionable group to use and abuse drugs. Drug abuse by Gen Z causes addiction, physical, mental and social health problems in the community, including disruptions in education, crime and death. Drug abuse among Gen Z teenagers certainly has an impact on Indonesia's national resilience, because it can endanger the life of the Indonesian people in the future. For this reason, the team feels need to conduct legal education about drugs in the form of legal counseling for students of SMA 1 Perhentian Raja with the aim that students realize the dangers and legal consequences of drug abuse and have a high commitment to say no to drugs as well as to realize to realize a gen Z that has legal awareness and anti-drug character.